FALLACIES IN THE BALANCE-SHEET APPROACH. - Myer, John N. (The Accounting Review, 1946)
Abstract During the twentieth century the approach used in the teaching of accountancy that has become almost universally accepted is that commencing with the balance sheet. Not only is the balance sheet the first topic discussed in the usual course in accountancy, but it is made the end and aim of all accounting and almost every step in the development of the accounting technique is taught with reference to its effect on the balance sheet. Although the balance sheet approach is convenient in teaching the mechanical details of accountancy, it does not equip the student with an understanding of the subject that will enable him later to interpret the results of the accounting processes. Elementary textbooks on accountancy, after commencing with a discussion of assets, liabilities, and net worth, proceed to explain how these are shown in a statement called the balance sheet. Probably the best explanation of a balance sheet is that it is a list of the balances of the accounts in the ledger of a business enterprise when its books of account have been closed. Such a definition it is, of course, impossible to give to the beginner since he presumably knows nothing about balances, accounts, ledger, or closing the books.